The Reporting of SDGs by Quality, Environmental, and Occupational Health and Safety-Certified Organizations - Fonseca, Luís (2019)
Organizations can play a significant role in the advancement of Sustainable Development, and companies with Quality, Environmental, and Occupational Health and Safety (QEOHS)-certified management systems address the three Sustainability Dimensions (economic, environmental, and social). This research aims to map the present level of engagement of those companies in contributing and reporting to the 17 Sustainable Development Goals (SDG) of the United Nations (UN) 2030 Agenda. By publicly disclosing their sustainability reports on their institutional websites, they can, therefore, support this agenda implementation. The content of the company reports that were available by 31 December 2017 in the institutional websites, from a total of 235 Portuguese organizations with QEOHS-certified management systems was analyzed. The results show a moderate reporting of SDGs by those companies, with the top five being SDG 12— Responsible consumption and production (23.8%); SDG 13—Climate action (22.1%); SDG 09—Industry, innovation, and infrastructure (21.3%); SDG 08—Decent work and economic growth (20.0%); and SDG 17—Partnerships for the goals (19.6%). The results of the statistical tests indicate that the communication of SDGs is more prominent in organizations (QEOHS) with the following characteristics: have a high business volume, are members of the United Nations Global Compact Network Portugal, and disclose their sustainability reports on their website. This study can be useful for both managers and decision makers who aim to support organizations in contributing to the Sustainable Development Goals and achieving a better and sustainable future for all.